A randomised-controlled trial investigating potential underlying mechanisms of a functionality-based approach to improving women's body image. (June 2018) - Alleva, Jessica M.; Diedrichs, Phillippa C.; Halliwell, Emma; Martijn, Carolien; Stuijfzand, Bobby G.; Treneman-Evans, Georgia; Rumsey, Nichola
Highlights: We conducted a randomised-controlled trial of the Expand Your Horizon intervention. Body complexity and body-self integration were tested as mechanisms of the effects. The intervention led to improved body image at Posttest, 1-week, and 1-month Follow-Up. The intervention improved body complexity, but it did not mediate intervention effects. Findings underscore the value of focusing on body functionality to improve body image. Abstract: Focusing on body functionality is a promising technique for improving women's body image. This study replicates prior research in a large novel sample, tests longer-term follow-up effects, and investigates underlying mechanisms of these effects ( body complexity and body-self integration ). British women ( N = 261) aged 18–30 who wanted to improve their body image were randomised to Expand Your Horizon (three online body functionality writing exercises) or an active control. Trait body image was assessed at Pretest, Posttest, 1-week, and 1-month Follow-Up. To explore whether changes in body complexity and body-self integration 'buffer' the impact of negative body-related experiences, participants also completed beauty-ideal media exposure. Relative to the control, intervention participants experienced improved appearance satisfaction, functionality satisfaction, body appreciation, and body complexity at Posttest, and at both Follow-Ups. Neither body complexity nor body-self integration mediated intervention effects. Media exposure decreased state body satisfaction among intervention and control participants, but neither body complexity nor body-self integration moderated these effects. The findings underscore the value of focusing on body functionality for improving body image and show that effects persist one month post-intervention.